2012
DOI: 10.1074/jbc.m112.387456
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphatase PTP-PEST/PTPN12 Regulates Endothelial Cell Migration and Adhesion, but Not Permeability, and Controls Vascular Development and Embryonic Viability

Abstract: Background: PTP-PEST is a phosphatase essential for embryonic viability. Results: PTP-PEST is critical for adhesion and migration of endothelial cells. Its absence in endothelial cells results in mouse embryonic lethality. Conclusion:The embryonic viability seen in constitutive PTP-PEST-deficient mice is due to a defect in endothelial cell functions. Significance: PTP-PEST is a key regulator of endothelial cell functions in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 43 publications
1
38
2
Order By: Relevance
“…PTPN12 tyrosine phosphatase was originally identified in a genetic screen for tumor suppressors in triple-negative breast cancers, where it inhibits multiple oncogenic tyrosine kinases, including HER2 and EGFR (49). In addition, studies of Ptpn12-deficient mice have shown that Ptpn12 regulates the migration of endothelial cells, dendritic cells, and macrophages, probably through dephosphorylation of Prk2, FAK, Cas, and paxillin (50)(51)(52). These antimigratory functions of PTPN12 also have been observed in several types of human cancers, including breast, ovary, and prostate cancers (53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…PTPN12 tyrosine phosphatase was originally identified in a genetic screen for tumor suppressors in triple-negative breast cancers, where it inhibits multiple oncogenic tyrosine kinases, including HER2 and EGFR (49). In addition, studies of Ptpn12-deficient mice have shown that Ptpn12 regulates the migration of endothelial cells, dendritic cells, and macrophages, probably through dephosphorylation of Prk2, FAK, Cas, and paxillin (50)(51)(52). These antimigratory functions of PTPN12 also have been observed in several types of human cancers, including breast, ovary, and prostate cancers (53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
“…Two mechanisms regulate the activation of Pyk2; the first, direct one, that leads to its initial autophosphorylation, is Ca 2ϩ -dependent, and the second involves dephosphorylation by various phosphatases (49), the tyrosine phosphatase PTP-PEST being a prime example. Regu- lation of Pyk2 by PTP-PEST has been described in a number of non-neuronal cellular contexts (29,50), and PTP-PEST has been shown to control dendritic arborization (52) by dephosphorylating Pyk2 and other proteins of the focal adhesion complex. PTP-PEST affects the phosphorylation status of a large set of proteins (53), and therefore, it is conceivable that PTP-PEST contributes an additional and currently unknown layer of complexity to fast CORT-triggered signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…It belongs to the PEST family, with PTPN22 and PTPN8 (3). PTPN12 can dephosphorylate several proteins, such as Cas, focal adhesion kinase (FAK), Pyk2, paxillin, Shc, and receptor protein tyrosine kinases (PTKs), and can regulate multiple cellular processes, including migration, adhesion, and receptortriggered proliferation (6)(7)(8)(9)(10)(11)(12).…”
mentioning
confidence: 99%